The impact of anthropogenic activities on Manis javanica Desmarest, 1822 (Mammalia: Pholidota: Manidae) in Sepanggar Hill, Malaysia - Nurasyiqin Awang Shairi; Julius Kodoh; Normah Awang Besar @ Raffie; Jephte Sompud (Wildlife Informaton Liaison Development Society, 2025)
The Sunda Pangolin, also known as Manis javanica Desmarest, 1822 (Pholidota: Manidae), is the only pangolin species found in Malaysia. This species is ‘Critically Endangered’ as per the IUCN Red List of Threatened Species and is among the most heavily trafficked mammals globally. Anthropogenic activities such as residential development and frequent human movement near forest edges have increasingly threatened the safety of the Sunda Pangolin. These activities not only lead to habitat fragmentation but also expose wildlife to elevated noise levels and human disturbances due to the proximity of settlements. Therefore, this study aims to determine the impact of anthropogenic activities that influences the distribution of Sunda Pangolins in Sepanggar Hill using camera trap survey method. Ten camera traps were set up in a systematic random design from May 2023–January 2024. The distances of nearest human settlements from the camera traps and anthropogenic noise level were also measured. The data from the camera traps and the anthropogenic noise level were collected every month. Over 2,724 trapping nights, camera traps captured five pangolin events. The Pearson correlation shows very weak correlations (-0.24 - 0.32) on the correlation of Sunda Pangolin presence and the proximity to the human settlements based on 2,741 data points. Despite high noise levels ranging 44.3 – 57.0 dB, Sunda Pangolins were detected more frequently near the first camera trap (N = 348, r = 0.147, p = 0.006**), an area with the highest anthropogenic noise, indicating a degree of noise tolerance. These findings highlight the adaptability of Sunda Pangolins to disturbed habitats as long as they do not feel threatened, but also underscore the necessity for targeted conservation efforts to mitigate more areas. Preserving quieter environments and reducing human impact is critical to ensure the survival of Sunda Pangolins in Sepanggar Hill. This research provides valuable insights for developing effective conservation strategies to protect this Critically Endangered species.